Fish functional diversity responses following flood pulses in the upper Paraná River floodplain. Issue 4 (26th March 2018) - Baumgartner, Matheus T.; de Oliveira, Anielly G.; Agostinho, Angelo A.; Gomes, Luiz C.
Abstract: Flood pulses are the main force driving the dynamics of aquatic communities in floodplains. The responses of communities to environmental changes following flood pulses usually demand a time lag to appear and reach the climax. We assembled a data set of 16 years of fish samplings to assess the relationship between water level and four functional diversity measures, in the upper Paraná River floodplain. Specifically, we approached four aspects of each relationship between water level and functional diversity: nature (positive or negative), sensitivity (response intensity), responsiveness (response delay) and extent (response duration). The nature of the relationship between water level and functional diversity was positive in all cases. Functional richness (FRic) responded right after flood pulses, although with shorter extent. Abundance‐dependent functional measures (evenness—FEve; divergence—FDiv; and Rao's quadratic entropy—Rao's Q) presented delayed responses, reaching peaks more than 1.5 years after flood pulses. Significant effects of floods on fish functional diversity were observed for more than 3 years, although the highest functional diversity was observed with 1.8 years, on average. More importantly, flood pulses had no longer significant effects on functional diversity after 4 years. Regarding conservation strategies in regulated systems, flood events should occur every 2 or 3 years, with adequate timing (October‐November), intensity (up to 450 cm) and duration (at least 50 uninterrupted days). Intervals longer than 3 years or inadequate timing, intensity and duration could dramatically decrease functional diversity and compromise ecosystem services.